Pandanus amaryllifolius Roxb (PEMANFAATAN DAN POTENSINYA SEBAGAI PENGAWET MAKANAN) - Dr. Marina Silalahi, M.Si (Jurnal Pro-Life, 2018)
Pandanus amaryllifolius Roxb. (pandan wangi) in long time ago has been used by human to preservation of food and beverage. This article is based on literature offline and online media. Offline literature used the books, whereas online media used Web, Scopus, Pubmed, and scientific journals. Pandan wangi has leaves not spiked and has been cultivated in the home garden. The pandan wangi in food and beverage industry to improve the flavour and colorant. The pandan aroma is the 2-acetyl-1-pyrroline (ACPY) which can be degraded by heating. The extract leaves pandan wangi has activity to inhibited the growth of bacteria that cause gastrointestinal disorder and food damage such as Shigella dysentriae, Staphylococcus aureus, Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. The P. amaryllifolius has potential as a natural food preservative.Keywords: antioxidant, antimicrobial , essential oil, Pandanus amaryllifotius